2022
DOI: 10.3390/foods11162542
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii in Foods: Prevalence, Control, and Safety

Abstract: Toxoplasma gondii is an obligate intracellular parasite that causes toxoplasmosis, with approximately one third of the population around the world seropositive. The consumption of contaminated food is the main source of infection. These include meat products with T. gondii tissue cysts, and dairy products with tachyzoites. Recently, contamination has been detected in fresh products with oocysts and marine products. Despite the great health problems that are caused by T. gondii, currently there are no standardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 215 publications
0
20
0
Order By: Relevance
“…Other biological hazards are constituted by certain groups of parasites such as Toxoplasma, Trichinella, etc., whose presence in fresh meat has been previously reported (Johne et al, 2021) revista del comité científico nº 36 AESAN Scientific Committee: Determination of the date of minimum durability for frozen meat in retail establishments (Marín-García et al, 2022). In this case, most of the studies on frozen meat show that its viability is significantly reduced at temperatures below -12 ºC (Kotula et al, 1991), although on many occasions it must be accompanied by a subsequent heat treatment to achieve a complete inactivation of these microorganisms.…”
Section: Foodborne Pathogensmentioning
confidence: 99%
“…Other biological hazards are constituted by certain groups of parasites such as Toxoplasma, Trichinella, etc., whose presence in fresh meat has been previously reported (Johne et al, 2021) revista del comité científico nº 36 AESAN Scientific Committee: Determination of the date of minimum durability for frozen meat in retail establishments (Marín-García et al, 2022). In this case, most of the studies on frozen meat show that its viability is significantly reduced at temperatures below -12 ºC (Kotula et al, 1991), although on many occasions it must be accompanied by a subsequent heat treatment to achieve a complete inactivation of these microorganisms.…”
Section: Foodborne Pathogensmentioning
confidence: 99%
“…During the 1950s and 1960s, investigations revealed that Toxoplasma can be transmitted through the consumption of undercooked or raw meat containing tissue cysts, particularly beef, lamb, pork, and venison can lead to T. gondii infection if the meat comprises tissue cysts. This discovery highlighted the significance of appropriate food processing and cooking practices to prevent the transmission of T. gondii to humans [42].…”
Section: Consumption Of Undercooked or Raw Meat Containing Tissue Cystsmentioning
confidence: 99%
“…Therefore, as in the case of listeriosis, immunocompromised populations, such as the elderly and pregnant persons (and their unborn offspring), are the primary populations at risk. The primary routes in which foodborne transmission of this disease occurs are via consumption of dairy products and undercooked meat or shellfish or other foods that have been improperly handled and have come into contact with undercooked meat or shellfish (Marín‐García et al., 2022). As such, 3DPF will likely not convey any additional risk when compared to traditional food preparation methods.…”
Section: Food Safety Aspects Of 3d Food Printingmentioning
confidence: 99%